Comparative analysis of MSME capital structure in Indonesia before and after the covid-19 pandemic - Ria Nelta Febriyanti; Eka Fitriyanti; Novita Sari (Indonesia Auditing Research Journal, 2025)
This study aims to compare the capital structure of MSMEs in Indonesia before and after the COVID-19 pandemic. Using a descriptive-comparative literature review based on secondary data from Statistics Indonesia (BPS), Otoritas Jasa Keuangan (OJK), Bank Indonesia (BI), and the Ministry of Cooperatives and MSMEs, this research finds a significant shift in financing strategies. During the pandemic, MSMEs relied heavily on internal and informal financing, while in the recovery phase, fintech lending and government-supported financing gained prominence. These findings align with pecking order and trade-off theories and indicate the necessity for adaptive financial policies and enhanced financial literacy to strengthen MSME resilience.